The Control of Postharvest Soft Rot Caused by Rhizopus stolonifer on Kokei No. 14 Organic Sweet Potato Roots by Carvacrol, Thymol, and Thyme Oil - Guangwei Wu; Chenqi Fan; Xueqian Zang; Bei Wang; Yanli Chen; Jingjing Kou; Guopeng Zhu (Foods)
Soft rotting caused by Rhizopus stolonifer is one of the most important postharvest decays in Kokei No. 14 organic sweet potato roots. While various methods have been explored for controlling this pathogen, there remains a need for effective, safe, and applicable alternatives, particularly using essential oils (EOs). This study evaluated the efficacy of EOs, specifically carvacrol, thymol, and thyme oil, in controlling Rhizopus soft rot. We conducted both in vitro and in vivo tests to assess their effects on fungal mycelial growth, spore germination, and the incidence and severity of soft rot in sweet potatoes, along with quality evaluations of the roots. The results indicated that the vapor phase of carvacrol, thymol, and thyme oil was more effective than the contact phase in inhibiting fungal growth and spore germination. In vivo tests revealed that all three EOs significantly reduced the incidence and severity of soft rot, with thymol and thyme oil at 300 mg/L, and carvacrol at 500 mg/L being the most effective. Quality assessments showed minimal impact on properties such as firmness, weight loss, color, starch, carotenoids, and flavonoids, although residual odors increased. GC/MS analysis confirmed that thyme oil contained high levels of both thymol and carvacrol, along with other antimicrobial compounds, suggesting that the cumulative activity of these volatile compounds enhanced their bacteriostatic effects. Thyme oil demonstrated greater efficacy in reducing soft rot development compared to its individual components, making it a promising biofumigant for controlling postharvest diseases in Kokei No. 14 organic sweet potato roots. These findings emphasized the potential for using thyme oil as a safe and effective approach to managing postharvest decay.